Myśl pedagogiczna Aleksandra Grozy. Wokół cyklu Elementarzy - Gruntkowska, Dominika (Biuletyn Historii Wychowania, 2023)
Aleksander Groza was the author of a series of three alphabet books: The greater alphabet book, The lesser alphabet book and The little alphabet book. This series was created in the Ukraine in 1860. Aleksander Groza was, first of all, a writer and poet, a representative of the so-called “Ukrainian school” in Polish literature, a nobleman and a representative of the middle-class gentry. The aim of the article is to characterize the alphabet books both in terms of structure and content. I will be interested in the values that Aleksander Groza intended to foster in his students, as well as how his ideas presented themselves against the epoch.